EROSI EKOLEKSIKON SUBAK PADAASPEK PALEMAHAN SEBAGAI AKIBAT DAMPAK NEGATIF DARI PERKEMBANGAN PARIWISATA - Murdana, I Ketut (Pusat penelitian & Pengabdian Kepada Masyarakat Politeknik Pariwisata Bali, 2011)
Ecolinguistics studies the interrelationships between language and environment. The environment refers to the relationships between both social and physical environment, as well as the relationships between language and culture. The Ecolinguistics and Dialectical theories view that the environment consists of Three Dimensions of Social Praxis, which are: Ideology, Sociology, and Biology Dimensions. The concept of Three Dimensions of Social Praxis is closely related to the concept of balance and harmony in life which is called Tri Hila Karana. This concept consists of three aspects, namely: Parhyangan Aspects (Spiritual Environment), Pawongan Aspects (Social Environment), and Palemahan Aspects (Natural Environment). The rapid development of tourism brings two major impacts to the environment, namely: positive and negative impacts. The negative impact will effect the existence of Subak as an inseparable part of Palemahan Aspect (natural or physical environment). The availability of ricefield or land is getting less and less as a result of land conversion process into tourism facilities, such as hotel, villa, and the like. Consequently, many ecolexicon of Subak will be eroded. In other words, erosion of Subak ecolexicon cannot be avoided.